2023
DOI: 10.3390/molecules28020903
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Pilot Study on Effects of Pomegranate Seed Oil Extract and Cosmetic Cream on Neurologically Mediated Skin Inflammation in Animals and Humans: A Comparative Observational Study

Abstract: The presence of phenobarbital and formaldehyde in drugs, food, and beverages can lead to various health issues, including inflammation, oncogenesis, and neurological distress. Psychological stress leads to mood fluctuations and the onset of skin inflammation. Skin inflammation has a range of causes, including chemicals, heavy metals, infection, immune-related disorders, genetics, and stress. The various treatments for skin inflammation include medical and cosmetic creams, diet changes, and herbal therapy. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…All other components were identified in trace amount. In an earlier study, hexane: ethanoic (3:1) extracts of pomegranate seed oil was analyzed by GC–MS, which identified 23 compounds, the majority of which belonged to fatty amides and fatty acids 24 . Another study has shown that pomegranate seed oils include polyunsaturated long-chain fatty acids as one of the primary components 25 .…”
Section: Resultsmentioning
confidence: 99%
“…All other components were identified in trace amount. In an earlier study, hexane: ethanoic (3:1) extracts of pomegranate seed oil was analyzed by GC–MS, which identified 23 compounds, the majority of which belonged to fatty amides and fatty acids 24 . Another study has shown that pomegranate seed oils include polyunsaturated long-chain fatty acids as one of the primary components 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Lifestyles, including the daily use of food, beverage, and cosmetic products, are considered an essential concern in modern functional medicine and the initiation of health problems. So, daily exposure to preservatives, pesticides, and other toxic ingredients, such as heavy metals, leads to their accumulation in many organs and may affect the chronological and vascular age of the human body [ 1 , 6 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We collected consent from all of the female volunteers. We grouped the female volunteers into two groups according to the questionnaire results: Group 1 ( n = 71), where they used cosmetic, food, and drink samples; Group 2 ( n = 29), where they did not use cosmetics, food, and drink samples that were included in this investigation [ 1 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pomegranate consists of various phytoconstituents having wide therapeutic potential such as effects against skin inflammations, diabetes, or flu infections (Hamouda & Felemban, 2023; Mansoor et al, 2018). Besides, it was shown that 5% (w/w) methanolic pomegranate peel extract had wound healing efficacy in guinea pigs (Hayouni et al, 2011).…”
Section: Skincarementioning
confidence: 99%
“…Pomegranate consists of various phytoconstituents having wide therapeutic potential such as effects against skin inflammations, diabetes, or flu infections (Hamouda & Felemban, 2023;Mansoor et al, 2018).…”
Section: Pomegranate (Punica Granatum L Family Punicaceae)mentioning
confidence: 99%